Small Posterior Cranial Fossa and Cerebellopontine Cistern Volumes Are Associated With Bilateral Trigeminal Neuralgia - Liu, Jiayu; Liu, Ruen; Liu, Bo; Zhou, Jingru; Fan, Cungang; Jiao, Feng; Wang, Dongliang; Li, Fang; Hei, Bo (Frontiers in Neurology, 2020)
Objective: To investigate whether small volumes of the posterior cranial fossa and cerebellopontine cisterns are risk factors for bilateral trigeminal neuralgia (BTN) and to provide further knowledge for the aetiology and treatment of this rare disease. Methods: We retrospectively analysed the clinical data and imaging examination results from 30 BTN patients between January 2009 and December 2019. Thirty age- and sex-matched healthy individuals and 30 patients with unilateral TN were selected as the two control groups. The volume of the posterior cranial fossa (VPCF) and the volumes of the cerebellopontine cisterns were measured using ITK-SNAP 3.0, which counted the cerebrospinal fluid (CSF) volume based on the region of interest (ROI). Preoperative and postoperative statuses were based on visual analogue scale (VAS) pain scores and BNI scores. Results: Three patients (10%) in the BTN group had familial trigeminal neuralgia, and there was no other hereditary history of neurological disorders in their families. Twenty-five (83.3%) patients had BTN on the left side and 26 (86.7%) on the right side. Veins were identified in the operative field and were regarded as the individual or the offending vessel. The mean VPCF was significantly lower in the patients with BTN than in the healthy control patients (p<0.05). Volumes of the cerebellopontine cisterns on both sides were significantly smaller in BTN patients than in healthy control patients (p<0.05). There was no significant difference between the BTN group and the unilateral TN group in terms of the VPCF (p>0.05), and there was no significant difference between the two groups in terms of the preoperative VAS pain scores or BNI scores. Conclusion: Small volumes of the posterior cranial fossa and cerebellopontine cisterns might be risk factors for BTN. Veins are the common offending vessels that cause BTN, which might be associated with abnormal vascular development leading to NVC. Microvascular decompression (MVD) is an effective treatment for BTN.